EMBEDDING STUDENTS’ POLITENESS THROUGH HABITUATION AT GRADE IV SDN SEROJA, SERANG - Iskini Haudoka; Suparno; Hosnan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The advancement of development nowadays has brought many positive and negative effects for everyone. The positive impact promotes progress in information and communication technology, whereas the negative impact can lead to setbacks in society, including the decline of politeness and mutual respect. Indonesia is well-known for its culture of manners and politeness, but recently this culture has begun to fade. For example, in several cases, students no longer consider their teachers as role models at school. Therefore, this research was intended to embed students’ moral and character through a habituation method. This method was expected to improve the students’ character.